Comparison Body Image and Physical Activity of Overweight and Non-Overweight Female Adolescents - Novitasari, Maryam (Universitas Nahdlatul Ulama Surabaya, 2025)
Adolescents, as human resources assets of a country, are vulnerable to health and nutrition problems, one of which is overweight. The prevalence of overweight in teenagers increases every year. Overweight during adolescence can increase the risk of non-communicable diseases and musculoskeletal disorders. Female adolescents are the key to the chain of life because they will become mothers in the future and pass on genetics to their descendants. Behaviour, lifestyle, nutritional adequacy, and sleep habits are determinants of adolescent overweight. This study aimed to examine the differences in body image and physical activity between overweight and non-overweight adolescent groups. The research design was a case-control study with 160 respondents aged 15-17 years in the city of Jambi in May 2023. Sample selection used a multistage sampling technique with inclusion criteria. BSQ and IPAQ are questionnaire scales used to measure individual body image and physical activity. Statistical tests used the Mann-Whitney test and Chi-Square. The Mann-Whitney test shows a difference in body image between overweight and non-overweight adolescents (p<0.05). However, there is no difference in physical activity between overweight and non-overweight adolescents. There is a significant relationship between body image and physical activity with overweight (p<0.05). Overweight adolescents have a negative body image; it is hoped that adolescents will exercise regularly and pay attention to their diet by consuming more nutritious and healthy foods. Keywords: Adolescent, body image, overweight, physical activity